Analysis of Mathematical Problem Solving Ability of Grade X Students at SMKN 2 Sarolangun in Terms of Adversity Quotient (AQ) - Ranti Oktiana; Muslimahayati Muslimahayati; Elis Muslimah Nuraida (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
This study aims to analyse the mathematical problem-solving abilities of Grade X students at SMKN 2 Sarolangun in terms of their Adversity Quotient (AQ), which consists of three types: Quitter, Camper, and Climber. The focus of the study is to determine the characteristics of students' problem-solving abilities for each AQ type. This study uses a qualitative descriptive approach with triangulation data collection techniques, including a questionnaire to measure students' AQ levels, a written test in the form of essay questions on the subject of Two Variable Linear Equation Systems (SPLDV) to measure problem-solving abilities, and interviews with students and teachers as supporting data. Data analysis was conducted in three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that the two students with the Quitter type had low AQ scores and demonstrated weaknesses in the problem-solving stage, particularly in understanding problems, formulating plans, and verifying results. The eight students with the Camper type had moderate AQ scores and were able to understand problems and formulate mathematical models correctly, but often stopped before reaching the final solution and rarely checked their work. Meanwhile, students with the Climber type, numbering 15, had high AQ scores and demonstrated the most comprehensive problem-solving abilities, from understanding problems, planning strategies, implementing systematic steps, to carefully checking their answers. Adversity Quotient plays an important role in distinguishing the level of resilience and quality of students' mathematical problem-solving